汉孟语法中的量词对比浅析 - Aga Mostafizur Rahman Chowdhury; Liu Ying (Sinolingua: Journal of Chinese Studies, 2026)
This paper presents a comprehensive cross-linguistic analysis of quantifiers in Bengali and Chinese. Bengali, a member of the Aryan branch of the Indo-Iranian language family within the broader Indo-European language group, and Chinese belonging to the Sino-Tibetan language family, exhibit distinct grammatical functions and expressions of quantifiers due to their profound linguistic differences. The research used a contrastive linguistic methodology and literature research to systematically analyze the categories, syntactic functions, and collocational patterns, etc. of quantifiers in the two languages, and explores the similarities and differences between the two languages. The results show that while quantifiers are used in both Bengali and Chinese to indicate quantity and classify nouns, there are notable differences between the two languages in terms of classification criteria, grammatical placement, and usage frequency. While Bengali tends to rely on a smaller, more broad collection of quantifiers, Chinese quantifiers are more numerous and particular, frequently determined by the shape, nature, or function of the word. Through meticulous comparative analysis, this research identifies both the similarities and differences in quantifier usage between the two languages. The study provides useful insights for language learners, especially those learning Chinese or Bengali as a second language, by underlining these differences. The findings may facilitate cross-linguistic research and instructional strategies enhance understanding of how actual quantification is structured in various languages.